Anti-inflammatory Activity of the Phenolic Compounds from Vanda roxburghii R. Br. - Ahammed, Md Salim; Kader, Md Abdul; Islam, K M Monirul; Lopa, Simin Shobnom; Alam, A H M K; Sadik, Golam (Bangladesh Pharmaceutical Journal, 2023)
Inflammation is implicated in the pathogenesis of several neurodegenerative diseases including Alzheimer’s disease (AD). Vanda roxburghii R. Br. is used as folk medicine in the treatment of various ailments and diseases including inflammation, rheumatoid arthritis and neurological disorders. We reported earlier that the plant possesses anti-inflammatory activity and the activity is high in the chloroform fraction among other fractions tested. Therefore, the present work was designed to isolate the compounds from the chloroform fraction responsible for anti-inflammatory activity. Four compounds namely syringaldehyde (1), vanillin (2), dihydroconiferyl dihydro-p-coumarate and (3) and gigantol (4) were isolated and purified using chromatographic methods. The isolated compounds were identified by analysis of their NMR spectral data. The compounds were evaluated for anti-inflammatory activity using carrageenan-induced hind paw edema model in mice. All the compounds showed significant activity at a dose of 100 mg/kg. Among the compounds, gigantol displayed the highest activity which was comparable to the activity of the standard drug indomethacin. At the same dose the other three compounds syringaldehyde, vanillin and dihydroconiferyl dihydro-p-coumarate exhibited similar activity. These results suggest that the isolated compounds from the chloroform fraction have potential anti-inflammatory activity that might be useful in the prevention and treatment of AD. Bangladesh Pharmaceutical Journal 26(1): 1-6, 2023 (January)